The Waterfall Method in Designing Information Management Applications Tri Dharma Lecturer - Juan Robert Sirait; Afian Syafaadi Rizki; Aidil Fajar Zulfahri; Dwi Agung Wibowo; Nina Mia Aristi; M. Najamudin Ridha (Institute of Computer Science (IOCS), 2022)
Information Technology is the use of computer equipment created to assist human work. Information technology itself covers various fields including the manufacture of hardware and software. The Tanah Laut State Polytechnic Information Technology study program really needs a system to manage the tri dharma activities of its teaching lecturers. This is caused by not optimal information about tri dharma activities which results in inaccurate reports, slow internal quality audit processes because it takes a long time to collect the required data. To overcome the existing problems a management application was built using the waterfall method. The waterfall method is a software development method that has several advantages including having a clear structure, being able to explain the final results of the software properly, and being informative. This application can help the study program manage information regarding the implementation of the tridharma of its lecturers.